Risk of overheating in low-rise naturally ventilated residential buildings of northeast India – an effect of climate change. (2nd January 2022) - Thapa, Samar
Abstract : The urban population in India is growing at a fast rate along with the growth in the construction of residential concrete houses. Though a majority of these residential buildings are still of naturally ventilated type due to the lower-middle-income group of the population, these buildings will be subjected to indoor overheating with climate change in future climatic years. This can cause severe thermal discomfort among the indoor occupants and reduce their well-being and satisfaction towards the indoor environment, and increase the possibilities of heat-related illness and even death. This paper presents the results of the effect of climate change on the thermal comfort of indoor occupants of low-rise naturally-ventilated buildings in two different physiographic and climatic regions of eastern India. The assessment methodology of indoor overheating hours and indoor overheating degree based on adaptive temperature limits are used to evaluate the indoor condition. Different simulation variants of archetypes, orientation, wall types, ventilation rates, roof types, etc. resulted in 13, 824 conditions. The results show that these concrete dwellings existing in the region are unable to suppress the effects of global warming and the indoor environment deteriorates in these buildings in future conditions. The decrease in the number of annual overcooling hours caused by the increasing ambient temperature due to global warming is lesser than the increase in the number of annual overheating hours, which ultimately results in the decline of the number of indoor annual comfortable hours.